Thinking working scaffolding sharing model to improve natural science competencies for biology pre-service teachers - Avia Riza Dwi Kurnia; Muslimin Ibrahim; Wahono Widodo (JPBI (Jurnal Pendidikan Biologi Indonesia), 2019)
Competencies of nowadays biology pre-service teacher is an important key for the future education quality. This article aimed to discuss the effectiveness of Thinking Working Scaffolding Sharing (TWSS) model implementaton in Departement of Biology UM. This quantitative descriptive study used learning outcomes (professional and pedagogical competencies), attitudes, and group activity of biology pre-service teacher as determinant factors of the TWSS model effectiveness. The instrument to collect the data for those parameters were product assessment and observation sheet. Universitas Negeri Malang assessment guideline was utilized to determine the pre-service teachers’ competencies; meanwhile, the percentage calculation was employed as the data analysis procedure to proceed the data. The results informed: 1) the mean values of learning outcomes for professional and pedagogical competencies were 94 and 74, respectively; 2) 92% of students showed individual responsibility in completing their tasks (in which 46% was categorized as ‘excellent’ and the other 46% was considered as ‘good’); 3) 85% of students performed excellent attitude in their group work. Therefore, the implementation of TWSS model is effective to improve natural science competencies for biology pre-service teacher.